CD44 genetic deletion enhances and CD44 antibody targeting attenuates autoimmune inflammation - Naor, David (Henry Stewart Talks, 2007)
CD44 and RHAMM (receptor for hyaluronan-mediated motility) are cell adhesion and cell homing receptors, Cell migration, Generation of different CD44 isoforms, RHAMM also supports cell motility and is engaged in intracellular signalling, Collagen-induced arthritis and type 1 diabetes are CD44-dependent pathologies, Molecular redundancy, CD44 targeting by anti-CD44 mAb may eradicate not only malignant cells and destructive inflammatory cells but also CD44-expressing normal cells which are committed to physiological functions
Reviewed at 2017/11/28